Akatemiasampo-portaali ja -datapalvelu henkilöiden ja henkilöryhmien historialliseen tutkimukseen - Hyvönen, Eero; Leskinen, Petri; Rantala, Heikki; Ikkala, Esko; Tuominen, Jouni (Informaatiotutkimus, 2021)
AcademySampo – Academic people in Finland 1640–1899 is a portal and a Linked Open Data service on the Semantic Web. AcademySampo contains richly interlinked open data about all people that have got academic education in Finland in 1640–1899. The system is targeted to researchers and the general public for biographical and prosopographical research. This review gives an overview on how AcademySampo can be utilized in practise with its novel digital humanities tools included in the portal and by using the data service via APIs.